2003
DOI: 10.1101/gad.1051603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of p53 loss on reversal and recurrence of conditional Wnt-induced tumorigenesis

Abstract: Aberrant activation of Wnt signaling is oncogenic and has been implicated in a variety of human cancers. We have developed a doxycycline-inducible Wnt1 transgenic mouse model to determine the dependence of established mammary adenocarcinomas on continued Wnt signaling. Using this model we show that targeted down-regulation of the Wnt pathway results in the rapid disappearance of essentially all Wnt-initiated invasive primary tumors as well as pulmonary metastases. Tumor regression does not require p53 and occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
196
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 37 publications
3
196
2
Order By: Relevance
“…Additionally, in our model 39% of the Tg DNbCat / þ , P53 þ /À animals display lung metastases. This was similar to the level found in the Wnt1 inducible system where 30% of the animals in the P53 þ /À background displayed metastases (Gunther et al, 2003). Although we do not observe a decrease in the number of apoptotic cells within the primary tumors of Tg DN-bCat / þ , P53 þ /À compared to Tg DN-bCat / þ , P53 þ / þ mice we cannot rule out the possibility that migrating cells survive more easily in the Tg DN-bCat / þ , P53 þ /À background due to impaired apoptosis induction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, in our model 39% of the Tg DNbCat / þ , P53 þ /À animals display lung metastases. This was similar to the level found in the Wnt1 inducible system where 30% of the animals in the P53 þ /À background displayed metastases (Gunther et al, 2003). Although we do not observe a decrease in the number of apoptotic cells within the primary tumors of Tg DN-bCat / þ , P53 þ /À compared to Tg DN-bCat / þ , P53 þ / þ mice we cannot rule out the possibility that migrating cells survive more easily in the Tg DN-bCat / þ , P53 þ /À background due to impaired apoptosis induction.…”
Section: Discussionsupporting
confidence: 85%
“…It is surprising that LOH at the wild-type P53 allele was observed in only one of 21 tumors because the single copy of P53 is sufficient to maintain genomic integrity (Donehower et al, 1995b;Venkatachalam et al, 1998). Interestingly, in the case of b-catenin-induced tumors, LOH occurs less frequently (only 4.5% of tumors) than in MMTV-Wnt1, P53 þ /À mice (50% of tumors) or Wnt1 inducible, P53 þ /À mice (19% of tumors) (Donehower et al, 1995a;Gunther et al, 2003). This difference may be partly due to the presence of intact b-catenin degradation machinery in these models, resulting in pressure to select mutated P53 alleles not present in the MMTV-DNb-catenin model.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that as tumors increase in size, they acquire additional genetic alterations that allow them to become independent of the initiating oncogene, IGF-IR. Regression rates observed with the 500 mm 3 tumors in the MTB-IGF-IR transgenics were similar to those observed in mammary tumors induced by Wnt1 (Gunther et al, 2003) or constitutively active ErbB2 (Moody et al, 2002) but considerably higher than regression rates observed in c-Myc-induced mammary tumors (D'Cruz et al, 2001;Boxer et al, 2004). The effect of tumor size on regression rates was not explored in these other doxycycline inducible mammary tumor models.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, theoretical concerns were raised about the reversibility of the malignant phenotype as consequence of inactivation of a single oncogene. However, experimental evidence suggest that cancer cells become 'addicted' to these genetic changes and, thus, inhibition of activated genes results in either growth arrest or cell death (Chin et al, 1999;Felsher and Bishop, 1999;Huettner et al, 2000;Gunther et al, 2003). Recent clinical experience proved that the concept of 'oncogene addiction' is true also for human tumors as shown, as an example, by the therapeutic targeting of the bcr-abl oncogene in Chronic Myelogenous Leukemia (Druker et al, 2001;Kantarjian et al, 2002;Vogel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%